Powdered Water - A Compact Solution for Drought Stricken Farms (International Journal of Current Engineering and Technology, 2014)
Droughts today are the biggest concern in today’s ever growing world due to various environmental factors such as global warming, greenhouse effect to site a few. Due to this very reason a new cure has been discovered to curb this problem. A super absorbent polymer known as “SOLID RAIN” can be used to reduce this problem that mainly arises during the summer and winter seasons in various tropical and sub- tropical countries in many parts of the world. In this paper we will be talking about potassium polyacrylate used in the manufacturing of solid rain and how this chemical is capable of soaking water upto 500 times its size. We will also be talking about the various advantages of this new technology and how this product may prove to be the world’s greatest success towards achieving an eco-friendly and ecological sustainable environment especially in the third world countries, so that future generations may also meet their needs.
Keywords: Droughts, potassium polyacrylate, soaking, super-absorbent and mechanism.